Home / Expert Answers / Advanced Math / nbsp-frac-c-s-r-s-frac-s-3-s-4-s-6-from-the-information-given-which-one-of-the-pa528

(Solved):   \[ \frac{C(s)}{R(s)}=\frac{s+3}{(s+4)(s+6)} \] From the information given which one of the ...



\[
\frac{C(s)}{R(s)}=\frac{s+3}{(s+4)(s+6)}
\]
From the information given which one of the following is the correct phase var

 

\[ \frac{C(s)}{R(s)}=\frac{s+3}{(s+4)(s+6)} \] From the information given which one of the following is the correct phase variable canonical form? \( \dot{x}=\left[\begin{array}{cc}0 & 0 \\ -10 & -24\end{array}\right] x+\left[\begin{array}{l}0 \\ 1\end{array}\right] r, \quad y=\left[\begin{array}{ll}3 & 1\end{array}\right] x \) \( \dot{b}=\left[\begin{array}{cc}-10 & -24 \\ 1 & 0\end{array}\right] x+\left[\begin{array}{l}1 \\ 0\end{array}\right] r, \quad y=\left[\begin{array}{ll}1 & 3\end{array}\right] x \) \( \dot{x}=\left[\begin{array}{cc}0 & 1 \\ -24 & -10\end{array}\right] x+\left[\begin{array}{l}0 \\ 1\end{array}\right] r, \quad y= \)


We have an Answer from Expert

View Expert Answer

Expert Answer


Given transfer function is C(s)R(s)=s+3(s+4)(s+6), Assume Y(s)=C(s). Y(s)R(s)=s+3(s+4)(s+6) [Y(s)X1(s)][X1(s)R
We have an Answer from Expert

Buy This Answer $5

Place Order

We Provide Services Across The Globe